A STUDY ON TEACHING ENGLISH FOR SPECIFIC PURPOSES TO ENGINEERING CLASS OF SMKN 1 MIRI, SRAGEN (A DESCRIPTIVE STUDY) - SOFYAN, ALI (2007)
This research is about the study on teaching English for Specific Purposes implemented in SMKN 1 Miri, Sragen. This research describes the strategies, and the difficulties in teaching English for Specific Purposes for Engineering class, and also the appropriateness between theory and practice of teaching English for Specific Purposes. This is a descriptive qualitative research. The teaching is implemented in the first year of Engineering class of SMKN 1 Miri, Sragen. The writer collects the data by observation, interview, and documentation. The strategies used by the teacher are the teacher always encourages the students to practice English, and not to be shy to speak English. The difficulties in teaching English for Specific Purposes are the lesson plan made by the teacher sometimes is not appropriate with the learning steps, and some of the students are not good in learning English. The theory and the practice of teaching English for Specific Purposes does not match because sometimes the recent curriculum ignore the students' needs, and the teacher's role is just as a teacher and an evaluator.